Consciousness, knowledge, and contextualized strategies according to necessities. - Mercedes del Sol Bonet; Clara Esther Gómez Gonzalvo; Lídice Angulo Valladares (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
The learning process at present must happen with a high responsibility in the students themselves accompanied by the technological support of information and communication. In this process, professors are facilitators for the students to obtain knowledge. This organizing flexibility is particularly important in the municipalización process, (i.e. to take the university studies to all the municipalities in our country), where profound changes are taken place no only in the educational scenario but also in the formation of the educational staff and its posterior development require further changes in its conceptions. An analysis of each context is imposed in this panorama in order to outline strategies which permit the optimum usage of the resources that are available in our health areas.